Satisfaction in Open Access Versus Traditional Referral for Upper Endoscopy in Children. Issue 5 (May 2015) - Isaac, Daniela Migliarese; Persad, Rabin; Huynh, Hien Q.; Shirton, Leanne; Turner, Justine M.
ABSTRACT: Objectives: In traditional access endoscopy (TAE), patients are booked for endoscopy following a gastroenterology clinic assessment. In contrast, open access endoscopy (OAE) patients are seen for the first time on the day of the procedure, providing same day procedural consent. Controversy exists over the use of OAE in adults, both with the consent process and with patient satisfaction. No literature exists describing satisfaction with OAE in pediatrics. We therefore aimed to assess pediatric patient and caregiver satisfaction in OAE compared with TAE. Methods: Consecutive pediatric patients, and their caregivers, undergoing elective upper endoscopy from May to December 2012 at the Stollery Children's Hospital (Edmonton, Alberta, Canada) were consented for a cross-sectional survey. Seven preprocedure and 5 postprocedure questions were completed regarding mood and satisfaction with the wait time and the information provided. Group demographics and endoscopy wait times were collected. Results: Median wait time with OAE was less compared with TAE (57 days vs 196 days, P < 0.001). OAE patients reported worse mood preprocedure than TAE patients (35.3% vs 10.7%, P = 0.046). OAE caregivers and patients reported more mood disturbance if required to wait longer for endoscopy by attending clinic preprocedure (OAE caregivers 62.2%, OAE patients 64.7%). Conclusions: OAE is associated with worse preendoscopy patient mood; however, children and caregivers seem concerned about longer wait times associated with TAE. Given the significantly shorter wait times in OAE, identifying methods to minimize present limitations of OAE will be useful to improve clinical practices in pediatric gastroenterology.